Cytomegalovirus ulcers following radiotherapy for a Marjolin ulcer in a renal transplant recipient. (6th September 2018) - Wang, Charlie Y; Mulley, William R; Dendle, Claire; Mar, Adrian
Abstract: Cytomegalovirus (CMV) infection represents a major cause of morbidity and mortality in immunocompromised hosts. Skin ulceration is a rare manifestation of tissue‐invasive disease, with the anogenital region being the most typical site of involvement. We present a case of CMV ulceration on the right leg occurring 16 years following renal transplantation and 1 year after adjuvant radiotherapy for a Marjolin ulcer at this site. We suggest radiotherapy may provide a mechanism for local reactivation of the virus in the skin of seropositive patients.